EFEKTIVITAS MEDIA POWER POINT UNTUK MENINGKATKAN HASIL BELAJAR MEMBACA PEMAHAMAN SISWA KELAS III SD INPRES PARANG MAKASSAR - Iramadhana Solihin (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2020)
This study aims to (1) examine the learning outcomes of students' reading comprehension in class III SD Inpres Parang Makassar using power point media; (2) assessing the learning outcomes of students' reading comprehension in grade III SD Inpres Parang Makassar without using power point media; (3) examining the effectiveness of power point media to improve learning outcomes for reading comprehension of third grade students of SD Inpres Parang Makassar. This study used an experimental research design with a posttest only control design. The population of this research is the third grade students of SD Inpres Parang Makassar. The data that had been collected were analyzed using descriptive statistical techniques and parametric inferential statistics type T Test that were processed using the SPSS version 20 windows computer program. The results of hypothesis testing show that (1) the value of t-count shows the number -9.708 with sig. (2 tailed) = 0.000. At the 95% significance level with 46 degrees of freedom. Because the significance value or p-value <0.005, then the null hypothesis (H0) is rejected or in other words the alternative hypothesis (H1) is accepted. Thus, it can be concluded that there is a significant difference between the pretest and posttest scores in the experimental class in the learning outcomes of students in class IIIB SD Inpres Parang Makassar. The use of power point media to improve students' reading comprehension learning outcomes of SD Inpres Parang Makassar is more effective using power point media. This can be seen from the t-test calculation of -9.708 with db = 46 at the 5% significance level. These results indicate that the price p = 0.000. The p value is less than 0.05.